RETAIL STORE DESIGN AND ENVIRONMENT AS BRANDING SUPPORT IN THE SERVICES MARKETING - Tudor NISTORESCU; Catalin Mihail BARBU (Management & Marketing)
The services are intangibles, therefore their quality is difficult to be evaluatedby the client and building a strong brand image is a challenging task. Theservices are distributed using diverse channels such as: company retailstores, dealers, franchise. The service companies are interested in theenvironment of the location, not only to increase sells but also in order toboost the image of the company. The excitement that a retail store induces toa client can modify the perception of the brand. The client values more abrand that distributes its services in a luxury, high-tech retail environmentthan a discount store. In this paper we intended to investigate the techniquesthat a service company is using to enhance the brand image in a retaillocation. For this purpose, the various aspects of the retail store design andenvironment were analyzed in connection with the customer-based brandequity model. This original association will offer the services companies’ newperspectives on how to leverage brand image.